Application of Story Telling Techniques to Improve Maharah Kalam Skills in Class XII IPA MA Maarif Roudlotut Tholibin Metro | Penerapan Teknik Story Telling untuk Meningkatkan Keterampilan Maharah Kalam di Kelas XII IPA MA Ma’arif Roudlotut Tholibin Metro - Baiti Sofiana; Lailin Khoirun Nabila; Endang Munawar (NAJAH BESTARI, 2023)
Speaking skills are the ability to pronounce a word or expression that is in each individual and involves aspects in the form of vocabulary and pronunciation structure. The purpose of speaking is to express a desire or feeling that is in each individual where all of that is obtained from the results of listening to or listening to a material or teaching material. Storytelling is a technique that can be chosen as a learning method in Arabic, especially in Maharah Kalam with the aim of improving the ability to speak Arabic in storytelling students or what is commonly interpreted as storytelling is one of the fun activities for students besides being able to stimulate the imagination of each student - Thus storytelling is able to develop the ability to speak Arabic in students and is able to explore the characteristics of the characters in the story being told. This research was conducted in class XII IPA MA MA'ARIF Roudlotut Tholibin using the Classroom Action Research method. The research model for this group trial was the Kemmis and Mc spiral model. Taggart. They divide the process of action research activities into one cycle, namely planning, acting, observing, and reflecting in a spiral system that is related between one phase and the next. Based on the research, there were changes in each student, which at first students had difficulty pronouncing words in Arabic, starting to become fluent even though they were not very fluent, students also became confident when standing in front of the class.